ابستمولوجيا الخطاب العلمي الجديد عند هنري بوانكاريه - باهي,محمد ياسين; طويل,كنزة (University of Eloued جامعة الوادي, 2024)
الملخص: تأسست العقلانية الغربية في العصر الحديث فكانت عبارة على رد فعل ثوري ضد التسلط الديني الذي مارسه رجال الكنيسة في العصور الوسطى هذا من جهة ومن جهة أخرى حيث كان العلم من أبرز مظاهر الحضارة الغربية في العصر الحديث و أكثرها تمثيلا ايجابيا لحضور الانسان الغربي حيث زاده العلم وعيا بالعالم و مكنه من أن يرسل نظرته العقلية إلى ما وراء الحدود التي تفرضها علينا الحواس هذا بالإضافة إلى أنه جعله أكمل شعورا بذاته حيث كشف له عن العلاقات التي تربطه بالبيئة البيولوجية و الاجتماعية و التاريخية كما أن التقدم السريع و التطور المفاجئ الذي أحرزته العلوم في شتى المجالات و بالتحديد في القرنين 19م و 20م خصوصا في ميدان فلسفة العلوم و ابستمولوجيا العلم و فيما يتعلق بالنظريات و مدى ما تحدثه من تغيير جذري في الحياة كل هذا أدى إلى حدوث ثورة علمية أصابت فلاسفة العلم و المناطقة بالدهشة و الاعجاب معا مما جعلهم يتوقفون عند دراستها محاولين توخي الحقيقة العلمية و المقصود هنا تلك الحقيقة البعيدة عن كل مثار للشك و المستقلة عن كل رؤية ذاتية و المختفية وراء الظواهر . نتج عن كل هذا ظهور نزعات و اتجاهات مختلفة في فلسفة العلم حاولت أن تفسر النظريات العلمية تارة و تبررها منطقيا ومعرفيا تارة أخرى ومن أبرز هذه النزعات نجد الابستمولوجيا المواضعاتية لهنري بوانكاريه . من خلال هذا التقديم يمكننا طرح الاشكالية الرئيسية : فيما تمثلت ابستمولوجيا الخطاب العلمي الجديد عند هنري بوانكاريه ؟ وهل استطاعت هذه الابستمولوجيا المقترحة من طرف بوانكاريه أن تكون فلسفة فعالة مواكبة للتطورات العلمية الحاصلة و اثراءا لهذا الموضوع طرحنا الاشكاليات الفرعية التالية : ماهي أهم مرتكزات الخطاب العلمي الكلاسيكي ؟ ماهي أهم العوائق الابستمولوجية للخطاب العلمي الكلاسيكي ؟ ماهي انعكاسات العلم المعاصر على الفكر الابستمولوجي ؟ تكمن أهمية هذا الموضوع في كونه حلقة تربط بين ماهو علمي وماهو فلسفي هذا من جهة ومن جهة أخرى فإن ابستمولوجيا المواضعاتية لهنري بوانكاريه تعتبر من النزعات التي مهدت الطريق للثورات العملية الكبرى خاصة في مجال الفيزياء و كذلك على مستوى المنهج وقد جاءت فلسفة العلم عند بوانكاريه لتمثل محاولة جديدة لإنقاذ العلم من بعض المفاهيم الكلاسيكية التي أدت إلى جمود العقل و افلاسه وتوقفه عن الابداع مثل مفاهيم الفيزياء الكلاسيكية كاليقينية و الحتمية و المكان المطلق و التي حلت مكانها مفاهيم النسبية و الاحتمالية و كان لبوانكاريه الفضل الأكبر في صياغة هذه الأسس حيث يقول : الاحساس بالنسبية هو احساس لا يمكن الافلات منه لأنه بمثابة قانون عام للطبيعة . Abstract: Western rationalism was established in the modern era, as it was an expression of a revolutionary reaction against the religious tyranny practiced by the men of the church in the Middle Ages, on the one hand, and on the other hand, as science was one of the most prominent manifestations of Western civilization in the modern era and the most positive representation of the presence of Western man, as science increased his awareness. of the world and enabled him to send his rational view beyond the limits imposed on us by the senses. In addition, it made him a more complete sense of himself, as it revealed to him the relationships that bind him to the biological, social, and historical environment, just as the rapid progress and sudden development that science has achieved in various fields. And specifically in the 19th and 20th centuries AD, especially in the field of philosophy of science and epistemology of science, and with regard to theories and the extent to which they bring about a radical change in life. All of this led to the occurrence of a scientific revolution that struck philosophers of science and logicians with both amazement and admiration, which made them stop studying it and try. Aiming for scientific truth, and what is meant here is that truth that is far from any cause for doubt, independent of every subjective vision, and hidden behind phenomena. All of this resulted in the emergence of different tendencies and trends in the philosophy of science that attempted to explain scientific theories at times and justify them logically and cognitively at other times. The most prominent of these tendencies is the positivist epistemology of Henri Poincaré. Through this introduction we can raise the main problem: What is the epistemology of the new scientific discourse according to Henri Poincaré? Was this epistemology proposed by Poincaré able to be an effective philosophy that keeps pace with the scientific developments taking place? In order to enrich this topic, we raised the following sub-problems: What are the most important foundations of classical scientific discourse? What are the most important epistemological obstacles to classical scientific discourse? What are the implications of contemporary science on epistemological thought? The importance of this topic lies in the fact that it is a link between what is scientific and what is philosophical. This is on the one hand, and on the other hand, the epistemology of positivism by Henri Poincaré is considered one of the tendencies that paved the way for major practical revolutions, especially in the field of physics, as well as at the level of method. Poincaré’sphilosophy of science came to represent an attempt New concepts to save science from some of the classical concepts that led to the stagnation of the mind, its bankruptcy, and its cessation of creativity, such as the concepts of classical physics, such as certainty, determinism, and absolute place, which were replaced by the concepts of relativity and probability. Poincaré had the greatest credit in formulating these foundations, as he says: The sense of relativity is A feeling that cannot be escaped because it is a general law of nature.
Keywords: الحتمية; ابستمولوجيا; المطلق-النسبية; الاحتمالية; Epistemology; classical scientific discourse; new scientific discourse; determinism; - absolute; relativity; NATURAL SCIENCES::Physics::Other physics::Theory of relativity, gravitation